Fatal frenzy - Force, Marie (Force, Marie. Fatal series, 2016)
Inauguration day is almost here ... Lieutenant Sam Holland is on leave, recovering from an attack that shook her to the core. With no case to distract her, she's trying to stay busy-- even voluntarily meeting with her new White House staff. But it's not enough to keep the horrific memories at bay, and her family is worried ... especially her husband, Vice President Nick Cappuano. Nick is dealing with his own demons where his wife's safety is concerned, losing night after night of sleep as he works to make sure what happened that day will never happen again. The pressure is building inside the Cappuanos' marriage, and something's got to give before Nick takes the oath of office. When two college girls go missing in the midst of inauguration madness, the chief of police needs the one cop he can count on to find them and save the Metro PD from disgrace. In a case full of ugly twists and turns, Sam will have to confront her past and find her strength ...